2019
DOI: 10.1007/978-3-030-16205-4_9
|View full text |Cite
|
Sign up to set email alerts
|

Improving Performance and Energy Efficiency of Geophysics Applications on GPU Architectures

Abstract: Energy and performance of parallel systems are an increasing concern for new large-scale systems. Research has been developed in response to this challenge aiming the manufacture of more energy efficient systems. In this context, this paper proposes optimization methods to accelerate performance and increase energy efficiency of geophysics applications used in conjunction to algorithm and GPU memory characteristics. The optimizations we developed applied to Graphics Processing Units (GPU) algorithms for stenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…They reached performance improvements of up to 10×. Pavan et al 37 proposed architecture‐based optimizations to improve the energy efficiency of geophysics applications running on NVIDIA GPUs. Their results showed that a combination of shared memory and reuse of registers improve performance and energy efficiency by up to 54.1%.…”
Section: Related Work and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…They reached performance improvements of up to 10×. Pavan et al 37 proposed architecture‐based optimizations to improve the energy efficiency of geophysics applications running on NVIDIA GPUs. Their results showed that a combination of shared memory and reuse of registers improve performance and energy efficiency by up to 54.1%.…”
Section: Related Work and Motivationmentioning
confidence: 99%
“…Pavan et al 37 and Calore et al 39 proposed different GPU optimizations to a stencil code evaluating performance and energy efficiency. We go beyond by assessing the portability of a real‐world application for different architectures and not only GPUs.…”
Section: Related Work and Motivationmentioning
confidence: 99%